Two high-BNI (biological nitrification inhibition) elite lines available for next users - CGIAR Research Program on Wheat (2021)
CIMMYT and JIRCAS demonstrated feasibility of enhancing BNI capacity in elite wheats by transferring a chromosome arm 3NsbS controlling BNI traits from wild grass as a wheat L. racemosus translocation chromosome (T3BL.3NsbS). Enhanced BNI release from root systems of T3BL.3NsbS resulted in suppression of soil nitrifier activity.